BIOSORPSI ION LOGAM BERAT Cu(II) DAN Cr(VI) MENGGUNAKAN BIOSORBEN KULIT KOPI TERXANTHASI - Renaldi Adriansyah; Elyn Novta Restiasih; Nessi Meileza (University of Bengkulu, 2018)
There are several methods that have been used to remove and reduce the contamination of heavy metal ions.Among theseveral methods, biosorpsi is a cheap and high efficiency method. One of the organic materials that have potential to become heavy metal ion biosorbent was coffee skin.However, to improve the performance of coffee skin in adsorption of heavy metal ions Cu (II) and Cr (VI) then biosorbent need to be modified through xanthation process.This xanthation process carried out by reacting the coffee skin with carbon disulfide compounds in an alkaline condition.This study aims to determine the ability of xanthated coffe skin biosorbentin adsorption of Cu (II) and Cr (VI) metal ions and to know the optimum condition of the metal ion adsorption process byxanthated coffe skin biosorbent. From this research we got the optimum mass of Cu (II) and Cr (VI) metal ion adsorption of 0.45 and 0.6 gram. The optimum pH of Cu(II) and Cr(VI) metal ions adsorption occurs at pH 4.While the optimum contact time occurs at 100 minutes for Cu (II )metal ion adsorption and 80 minutes for Cr (VI) metal ion adsorption. In addition, the maximum biosorption capacity of xanthated coffeskin biosorbent in adsorption of Cu (II) and Cr(VI) metal ions respectively 62.5 mg/g and 8.064 mg/g. So it can be concluded that xanthated coffe skin biosorbenthave a better ability to adsorb Cu (II) metal ions than Cr (VI) metal ions.